Implementasi kegiatan ekstrakulikuler khitobah untuk menumbuhkan rasa percaya diri siswa di MI Al Khairiyyah 01 Semarang - Ulya, Maulina Hidayatul; Najichah, Amalia Fajriyyatin (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to examine the role of extracurricular khitobah at MI Al Khairiyyah 01 Semarang in building self-confidence and nurturing young preachers as a strategy for instilling Islamic values from an early age and developing public communication skills in elementary school children. The research uses a qualitative approach to capture meanings, experiences, and social dynamics that cannot be measured quantitatively. Data collection techniques were carried out through participatory observation and interviews. The research location was at MI Al Khairiyyah 01 Semarang, which is the center for the implementation of the khitobah extracurricular program. The results show that this activity not only attracts students' interest but also becomes an important pillar in shaping a young generation that is confident, articulate, and morally upright. The mimicry memorization method was strategically applied as a first step in mastering basic speech techniques by imitating and memorizing according to the teacher's instructions. Although its implementation faced several challenges, the application of this method was responded to through contextual and adaptive solutions. The integration of khitobah with the school curriculum made it a vehicle for shaping Islamic character, public literacy, and 21st-century competencies.